Model Hidrologi Produksi Air Bulanan Bagian I : Kalibrasi dan Analisis Kepekaan - Lukman Hidayat; Putu Sudira; Sahid Susanto (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 1996)
In a hydrologic model, sensitivity analysis is essential in order to determine the importance of parameters on model outputs, and to expIore more completely the validity of the model. The study focused on calibrating and the sensitivity analysis of hydrologic model parameters. A monthly water yield model of rainfall-runoff relationship has been created in order to simulate runoff volumes. It was controlled by four parameters, those are: fo (infiltration capacity, mm/hr), Mc(the moisture-holding capacity of the lower zone, mm), Sm (maximum possible seepage rate, mm/day), and a (a constant defining the portion of seepage that appears as runoff). An automatic parameter optimization routine was presented. Eleven small watersheds (less than 1000 square km) in Central Java were used for calibration. The results of sensitivity analysis showed that the increasing value of Fo and Mo will be followed by the decreasing of model output (water yield). In contrast, the increasing value of Sm and a will be followed by the increasing of model output Fo more sensitive than Mc, Sm, and a.Based on graphical and statistical criteria, the monthly water yield can be simulated well by the model.